(untitled) (Konturen, 2010)
Feminists, including this one, have two problems with nature: a special problem which is a historical and political problem, and an ontological problem that we share with everyone else (our metabolism with the earth). My claim is that the first problem is so acute that it tends to make us forget the second. The fundamental division in contemporary feminist thinking can be described as that between feminists who are interested in deconstructing, all the way down, the notion of natural differences between women and men as pre-social, and feminists who are interested in recuperating, re-affirming or asserting some version of originary sexual difference. By returning to Simone de Beauvoir, we find that even at this early moment in contemporary feminist thought a more complex account of nature was already articulated. Beauvoir helps us understand how structures of injustice are parasitically entangled with general features of human existence, even those that seem most “natural.” At one founding moment of contemporary feminist thinking, then, deconstructive and descriptive engagements with the question of nature, far from being opposed, are co-necessary features of feminist thought.